1989
DOI: 10.1083/jcb.109.6.3073
|View full text |Cite
|
Sign up to set email alerts
|

The cytomechanics of axonal elongation and retraction.

Abstract: Neurites of PC12 and chick dorsal root ganglion neurons behave as viscoelastic solids in response to applied forces. This passive behavior can be modeled with three mechanical elements; a relatively stiff, undamped spring in series with a Voight element composed of a less stiff spring in parallel with a dashpot. In response to applied tensions greater than 100 microdynes, PC12 cells show lengthening behavior distinct from and in addition to the passive viscoelastic response. We interpret this as "towed growth"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
276
1
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(308 citation statements)
references
References 33 publications
27
276
1
4
Order By: Relevance
“…The mechanisms of molecular and cellular function in morphogenesis are defined in terms of the biomechanical and geometric context of cell populations (see Hardin, 1990). Although regorous biomechanical analysis at cell-cell population level is just beginning, progress is being made with both experimental and modeling approaches (see Koehl, 1990;Dennerll et al, 1989;Adams, et al, 1990;Koehl et al, 1990;Jamney, et al, 1991;Moore, 1992;Weliky et al, 1992), and it is important that this field be developed in order to understand the mechanisms of morphogenesis at any level.…”
Section: The Importance Of Understanding Regional Autonomy and Regionmentioning
confidence: 99%
“…The mechanisms of molecular and cellular function in morphogenesis are defined in terms of the biomechanical and geometric context of cell populations (see Hardin, 1990). Although regorous biomechanical analysis at cell-cell population level is just beginning, progress is being made with both experimental and modeling approaches (see Koehl, 1990;Dennerll et al, 1989;Adams, et al, 1990;Koehl et al, 1990;Jamney, et al, 1991;Moore, 1992;Weliky et al, 1992), and it is important that this field be developed in order to understand the mechanisms of morphogenesis at any level.…”
Section: The Importance Of Understanding Regional Autonomy and Regionmentioning
confidence: 99%
“…Axons can reach a metre or more in length, indicating that the elongation involves growth induced by axial tension Gilbert 2003). Using flexible needles, Dennerll et al (1989) measured the tension in axons from dorsal root ganglion neurons of chick embryos. After attaching one end of a needle to the growth cone, they lifted it from the substrate and held the axon at a relatively fixed length until the force equilibrated.…”
Section: Counterexample: Rapid Shortening Of An Axonmentioning
confidence: 99%
“…Furthermore, a linear relationship existed between the growth rate and the experimentally applied tension, and the axonal growth was regulated by mechanical tension. [1][2][3][4][5] Interestingly, the result of our present study suggested that it is also possible to lengthen the regenerating sprouts of the transected proximal nerve stump by the mechanical stretching. Thus, the stimulus of mechanical stretching also induces the growth of regenerating sprouts in vivo.…”
Section: Stretching Of the Proximal Stump Induces The Growth Of Sproutsmentioning
confidence: 67%
“…In addition, it has been reported that tension applied to the growth cones of PC12 or chick DRG neurites can induces a significant neurite outgrowth. [1][2][3][4][5] In our previous studies, we lengthened the transected proximal nerve stumps by direct gradual stretching ex vivo, and the whole nerve trunk including the endoneurium and axons were lengthened simultaneously in proportion to the stretching period. Interestingly, however, in our experiment the tip of the proximal nerve stump was significantly lengthened during gradual stretching.…”
mentioning
confidence: 99%